Dignity in care: where next for nursing ethics scholarship and research? - Ann Gallagher; Elma Lourdes Campos Pavone Zoboli; Carla Ventura
Dignity is recognised as both a central and also a contested value in bioethics discourse. The aim of this manuscript is to examine some of the key strands of the extensive body of dignity scholarship and research literature as it relates to nursing ethics and practice. The method is a critical appraisal of selected articles published in Nursing Ethics and other key manuscripts and texts identified by researchers in the UK and Brazil as influential. The results suggest a wide and rather confusing range of perspectives and findings albeit with some overall themes relating to objective and subjective features of dignity. In conclusion, the authors point to the need for more sustained philosophical engagement contextualising human dignity within a plurality of professional values. Future empirical work should explore what matters to patients, families, professionals and citizens in different cultural contexts rather than foregrounding qualitative research with such a contested concept.